2006
DOI: 10.1183/09031936.06.00080105
|View full text |Cite
|
Sign up to set email alerts
|

Allergic lung inflammation induces pulmonary vascular hyperresponsiveness

Abstract: Pulmonary arterial vasoconstriction is an important early component of pulmonary hypertension. Inflammatory mechanisms play a prominent role in the pathogenesis of pulmonary hypertension. The present authors investigated the potential role of acute allergic lung inflammation for alterations in pulmonary haemodynamics.BALB/c mice were intraperitoneally sensitised to ovalbumin and challenged by ovalbumin inhalation. Subsequently, lungs were ventilated and perfused ex vivo, and pulmonary arterial pressure (Ppa) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
22
1
1

Year Published

2007
2007
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 52 publications
7
22
1
1
Order By: Relevance
“…Increased pulmonary arterial vascular tone is an important early component of pulmonary vascular disease [14]. It has been demonstrated that a specific antigen challenge causes an increase in responsiveness to contractile agonists [14] and a decrease of endothelium-dependent relaxant responses to acetylcholine [15,16]. Published data confirm that damage to the endothelium may play an important role in the development of pulmonary vascular diseases in both humans and experimental models [17,18].…”
Section: Vascular Tonesupporting
confidence: 50%
See 1 more Smart Citation
“…Increased pulmonary arterial vascular tone is an important early component of pulmonary vascular disease [14]. It has been demonstrated that a specific antigen challenge causes an increase in responsiveness to contractile agonists [14] and a decrease of endothelium-dependent relaxant responses to acetylcholine [15,16]. Published data confirm that damage to the endothelium may play an important role in the development of pulmonary vascular diseases in both humans and experimental models [17,18].…”
Section: Vascular Tonesupporting
confidence: 50%
“…We compared its effects in normal rats and in two experimental model rats that combine the inflammation and endothelial dysfunction of pulmonary vessels: the ovalbumin (OVA)-induced allergic airway disease and monocrotaline (MCT)-induced pulmonary hypertension. Increased pulmonary arterial vascular tone is an important early component of pulmonary vascular disease [14]. It has been demonstrated that a specific antigen challenge causes an increase in responsiveness to contractile agonists [14] and a decrease of endothelium-dependent relaxant responses to acetylcholine [15,16].…”
Section: Vascular Tonementioning
confidence: 99%
“…29 Some cytokines also alter the amounts of various surface components of the blood vessel wall and significantly decrease the functional cell surface thrombin receptor (thrombomodulin), thus promoting coagulation in the pulmonary vessels. 30 Other changes in the inflammatory process may cause endothelial dysregulation of cell-cell adhesion and transendothelial migration, which contribute to the pulmonary vasculopathy.…”
Section: Immunological Modulation Of Schistosomiasis and Its Effect Omentioning
confidence: 99%
“…In contrast to other animal models of allergic respiratory disease that used the i.p. route for sensitization (8,34), this model was completely intranasal for sensitization, boost, and challenge, and as such better mimics the route through which human respiratory sensitization to allergens occurs. Furthermore, this model was adjuvant-free and thus the immune responses observed were due entirely to Ag exposure and were not skewed by the use of adjuvants such as aluminum hydroxide.…”
Section: Discussionmentioning
confidence: 99%